Some Schiff's Base Complexes of Antimony(III). - Rastogi, M.K. (Asian Journal of Chemistry, 2010)
Some Schiff's base complexes of antimony(III) have been prepared using antimony trichloride and triiodide separately. The Schiff's base ligands have been obtained by condensation of salicylaldehyde with amines (ethylamine, aniline, o-toluidine), amides (acetamide,benzamide) and ureas (urea, thiourea). It has been observed that the complexes are readily formed just on slight warming. In case of antimony triiodide, two iodines are readily attacked but in case of antimony trichloride all the three chlorines are attacked. The complexes with urea and thiourea involve macrocyclic Schiff's base ligands.